Penjadualan kerja berkala jururawat menggunakan kaedah pengaturcaraan gol 0-1 - Wan Rosmanira Ismail,; Ruzzakiah Jenal,; Liong, Chong Yeun; Mohd Khairi Muda, (Universiti Kebangsaan Malaysia, 2009)
The continuous provision of nursing service to patients is an important task. The continuity of services, i.e. 24 hours a day 7 days a week needs shifts working environment that may affect the changes in nurses’ daily social life and may cause health problems. Thus, the development of a quality nurse rostering model that is acceptable and fair to everyone is a must in order to ensure there is quality in this continuous service. Rostering process involves some rules and constraints based on hospital’s policies and nurses’ preferences. The hospital’s policies or objectives among others are to ensure the minimum number of nurses on duty for each shift, to avoid any isolated days on and to consider the nurses request for annual leave. Meanwhile the nurses’ preferences are having the same number of days on per schedule, the number of morning shifts more than the evening shifts and at least 1 day off during weekend for 2 weeks planning period. The developed model is illustrated on data from a local hospital. A 0-1 goal programming technique is applied to building the nurse rostering model because of its ability to produce the model with multiple objectives. This work schedule will be generated every 2 weeks. The result obtained by Lingo software shows that the developed nurse rostering model fulfilled the hospital’s policies and the nurses’ preferences. This rostering model is considered to perform better than the current manually developed schedule where the distributions of shifts are more even among the nurses in terms of the number of morning, afternoon and night shifts.